2022
DOI: 10.3390/nu15010171
|View full text |Cite
|
Sign up to set email alerts
|

A Pleiotropic Nuclear Hormone Labelled Hundred Years Ago Vitamin D

Abstract: This year we are celebrating 100 years of the naming of vitamin D, but the molecule is, in fact, more than one billion years old [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Timmers et al noted that 40% of the children had deficient levels and 38% insufficient levels [42]. Furthermore, in our series, two heterozygous adults had severe hypovitaminosis D. Severe deficiency can cause bone malformations in children (rickets) and adults (osteomalacia) [19,47], and it can dramatically increase the risk of mortality, infections, and many other diseases [48].…”
Section: Vitamin Dmentioning
confidence: 54%
See 1 more Smart Citation
“…Timmers et al noted that 40% of the children had deficient levels and 38% insufficient levels [42]. Furthermore, in our series, two heterozygous adults had severe hypovitaminosis D. Severe deficiency can cause bone malformations in children (rickets) and adults (osteomalacia) [19,47], and it can dramatically increase the risk of mortality, infections, and many other diseases [48].…”
Section: Vitamin Dmentioning
confidence: 54%
“…In CF patients, Vit-D is essential for bone, immune, gastrointestinal (GI) and lung health [18]. At any age, Vit-D deficiency can cause immunodeficiency disorders, with the consequent risk of infectious, as well as the occurrence and progression of autoimmune diseases [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The value of 30 ng/mL corresponds to the minimum plateau value of PTH and, therefore, should be fine with regard to the skeletal action of vitamin D. However, there are extraskeletal effects of vitamin D. These non-skeletal effects occur at concentrations higher than 30 ng/mL, probably between 40 ng/mL and 60 ng/mL [20]. It has been reported that concentrations above 50 ng/mL can increase the expression of VDR mRNA [9] and that calcitriol binds to VDR with a K d of 0.1 nM [7]. So, at higher concentrations, vitamin D binds to its receptor and forms a heterodimer with the vitamin A receptor, exerting its anti-inflammatory action.…”
Section: Low Levels Of Vitamin D Could Be a Marker Of Potential Predi...mentioning
confidence: 99%
“…In fact, we must consider that the active form of vitamin D 3 behaves like a hormone by binding to a nuclear receptor/transcription factor, called VDR, which has numerous pleiotropic effects at the level of the immune, cardiovascular, neurological, and intestinal systems [5][6][7]. These effects, which have not yet been taken into due consideration by government institutions, are often associated with the inflammatory diseases of our time.…”
Section: Introductionmentioning
confidence: 99%
“…The role of vitamin D deficiency in initiating and aggravating the course of inflammatory dermatoses is well documented; the same is true for the beneficial effects of its supplementation [ 137 , 138 , 139 ]. However, low vitamin D levels could hardly be viewed as a nutritional deficiency because “vitamin D” is in fact a group of nuclear hormones with pleiotropic actions, including immunomodulation [ 140 , 141 , 142 ]. Under favorable circumstances, all active forms of vitamin D are synthesized entirely in the body; therefore, low levels of vitamin D should be viewed as a hormonal disorder rather than nutrient deficiency [ 143 ].…”
Section: An Overview Of Diseases From the Spectrummentioning
confidence: 99%